Impact of the novel square wave tool path pattern on AA6061-T6 friction stir welding. Issue 8 (11th June 2022) - Jayaseelan, V.; Jayabalakrishnan, D.; R, Ashok Gandhi; Muthuramalingam, T.; Francis Xavier, J.
ABSTRACT: The proposed study deals with the joining of AA6061 T6 alloy using a novel geometric square wave tool path pattern for adequate mixing of materials with increased stirring time and enlargement of the deformation zone. Experiments were conducted based on the process parameters to imply the stirring effect like rotation speed 1200 rpm, weaving rate 100 mm/min; and specific step sizes (1.0, 1.5, and 2.0 mm). Results show that the Percentage of variation for achieving the higher tensile strength of 11.3%, micro vickers hardness of 12.8% with a step size of 1 mm compared to the linear weldment. The SEM morphologies of the weldment clarify the formation of IMCs like spheroidal cementite with the zeolitic structure for resulting in higher hardness value. The EDAX results confirm the formation of intermetallic precipitates like Mg2 Si that leads the precipitation hardening and grain boundary strengthening.